WORK PROCESSES AND INTERVENTION OF SOCIAL WORKERS IN THE RNCCI: AN EXPLORATORY STUDY IN THE NORTHERN REGION OF PORTUGAL ("Temas Sociais" Journal, 2025)
The aim of this article is to demonstrate the work processes and intervention of social workers in the National Network of Integrated Continued Care (RNCCI) in the North region of Portugal. As part of multidisciplinary teams, these professionals develop practices anchored in a holistic approach to health understood as a biopsychosocial and spiritual process. They draw up social diagnoses, plan, monitor and evaluate interventions with the aim of ensuring continuity of care in the community. In order to achieve this objective, a questionnaire was administered to fifty-two social workers who work in the RNCCI (North) in an inpatient setting. The results show that these professionals feel they have good working conditions despite the overload, low salaries and lack of professional career progression. In their intervention, they are faced with challenges relating to the emergency planning of discharges associated with the management of social cases and the fragility of formal and informal resources that ensure continuity of care in the community. The multidisciplinary team values the role that these professionals play in resolving complex social situations but does not always recognise their knowledge of the welfare system and public policies. It is therefore considered urgent to value and equip these professionals with critical and reflective skills that will enable them to tackle these obstacles by promoting actions that value the profession in the RNCCI, adopting practices adjusted to the complexity of the situations, in accordance with the needs of the beneficiaries of the services ensuring the continuity of quality integrated care in a community context.